2014
DOI: 10.1134/s0036029514080084
|View full text |Cite
|
Sign up to set email alerts
|

Stationary anodic process at platinum in KF-NaF-AlF3-Al2O3 melts

Abstract: The kinetics of the anodic process at platinum in KF-NaF-AlF 3 -Al 2 O 3 melts in the temperature range 725-800°C is studied using potentiostatic polarization. Platinum is considered as an indifferent oxy gen evolving electrode, and a two stage scheme is proposed for the anodic process on it. According to this scheme, primary charge transfer with the formation of adsorbed O ads particles is accompanied by their des orption according to a physical or an electrochemical mechanism. The polarization dependences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The gas CO/CO 2 electrode was used as a quasi-reference one. 21 The gas CO/CO 2 electrode was realized by placing the graphite rod (forming the electrode substrate) in the porous sintered alumina case (OJSC "Ogneupory", open porosity -1.2 vol. %) containing the CaCl 2 -CaF 2 melt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas CO/CO 2 electrode was used as a quasi-reference one. 21 The gas CO/CO 2 electrode was realized by placing the graphite rod (forming the electrode substrate) in the porous sintered alumina case (OJSC "Ogneupory", open porosity -1.2 vol. %) containing the CaCl 2 -CaF 2 melt.…”
Section: Methodsmentioning
confidence: 99%
“…We encountered this problem earlier when studying the anode process on platinum in oxide-fluoride melt. 21 The aim of this work was to obtain additional experimental data to support a further discussion of the mechanism underlying the processes occurring at the inert cathode in molten CaCl 2 -CaF 2 containing Al 2 O 3 by means of cyclic and square-wave voltammetry as well as z E-mail: suzdaltsev_av@mail.ru electrolysis tests in two laboratory electrolyzers supplied with different types of anolyte-catholyte separation.…”
mentioning
confidence: 99%
“…The anodic processes on glassy carbon and platinum, as well as degradation processes on oxygen-evolving anodes in low-melting NaF-AlF3-Al2O3 and KF-AlF3-Al2O3 systems are discussed in [2][3][4][5][34][35][36][37][38]. On the basis of resource tests, it was shown that lowering the temperature to 750-800 °C favourably affects the corrosion resistance of oxygen-evolving anodes, and the study of the anodic process on them seems relevant.…”
Section: Anodic Processmentioning
confidence: 99%
“…Experiments were performed in alundum crucible [4], which was placed in a quartz cell purged with argon or oxygen. The auxiliary nichrome electrode was placed in a porous alundum tube that serves as a diaphragm.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier [4] a comparative analysis of experimental and modeling stationary polarization curves for platinum in KF-NaF-AlF 3 …”
mentioning
confidence: 99%